The Federal Democratic Republic of Ethiopia : 2019 Article IV Consultation and Requests for Three-Year Arrangement under the Extended Credit Facility and an Arrangement under the Extended Fund Facility-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2020)
This paper presents 2019 Article IV Consultation with the Republic of Ethiopia and its Requests for Three-Year Arrangement Under the Extended Credit Facility and an Arrangement Under the Extended Fund Facility. Ethiopia has enjoyed strong growth for over a decade, which has reduced poverty and raised living standards. However, the public investment-driven growth model has reached its limits. The authorities have announced a Homegrown Economic Reform Plan, consisting of a mix of macroeconomic, structural and sectoral policies, to address vulnerabilities and tackle structural bottlenecks inhibiting private sector activity. Over the medium term, macroeconomic and structural reforms announced by the authorities are expected to lead to a reduction in public debt, lower external vulnerabilities, and stronger growth, investment and exports. The risks to the outlook are tilted to the downside. Domestic opposition to reforms ahead of the upcoming elections could increase investor uncertainty and weigh on investment and growth. External risks stem from rising protectionism and weaker than expected global growth as well as climate-related shocks.